Safety and Efficacy of Vacuum-Assisted Breast Biopsies under Ultrasound and Stereotactic Guidance - Thakkar Popat, Palak Bhavesh; Karbhari, Aashna; Shetty, Nitin; Gala, Kunal; Haria, Purvi; Katdare, Aparna; Chauhan, Sonal; Parmar, Vani; Nair, Nita; Joshi, Shalaka; Desai, Sangeeta; Shet, Tanuja; Patil, Asawari; Sahay, Ayushi; Thakur, Meenakshi; Badwe, Rajendra; Kulkarni, Suyash (Journal of Clinical Interventional Radiology ISVIR, 2023)
Purpose To evaluate the safety and efficacy of vacuum-assisted breast biopsy (VABB) under ultrasound and stereotactic guidance.Methods This institutionally approved retrospective analysis comprised 60 females who underwent VABB under ultrasound and stereotactic guidance. Technical success and adverse events were analyzed as per the Society of Interventional Radiology standards. Pain score was recorded as per the visual analog scale.Results Technical success was 100% with high specificity (100%), sensitivity (96%), negative predictive value 97%, and accuracy of 98%. Ductal carcinoma in situ underestimation rate was 4%. No major complications were encountered, and minor complication of postprocedural hematoma did not require intervention. Procedure was well tolerated with majority patients experiencing mild pain.Conclusion VABB under ultrasound and stereotactic guidance is a safe and effective method for sampling breast abnormalities.
Keywords: breast; intervention; biopsy; vacuum-assisted biopsy